AB0562 SLEEP HYGIENE: COULD IT BE A CONFOUNDING FACTOR FOR SLEEP QUALITY IN SYSTEMIC SCLEROSIS?. (2nd June 2020) - Gokcen, N.; Komac, A.; Tuncer, F.; Yazici, A.; Cefle, A.
Abstract : Background: Sleep disturbances have been described in Systemic Sclerosis (SSc). Confounding factors related to sleep quality are also investigated. Although sleep hygiene plays an important role in sleep quality, as far as we know, there are not enough data to show the effect of sleep hygiene on sleep quality of SSc. Objectives: To investigate sleep hygiene, its impact on sleep quality, and its association with demographic-clinical factors in patients with SSc, rheumatoid arthritis (RA), and healthy controls. Methods: The study was designed as cross-sectional. Forty-nine patients with SSc who fulfilled the 2013 ACR/EULAR classification criteria for SSc, 66 patients with RA who fulfilled 1987 revised classification criteria, and 30 healthy controls were included in the study. All participants were female. Demographic and clinical variables were documented. Disease activity index of both SSc and RA was calculated. SSc patients were assessed by questionnaires including Short Form 36 (SF-36), The Health Assessment Questionnaire Disability Index (HAQ-DI), Beck Anxiety and Beck Depression Inventory, Pittsburg Sleep Quality Index (PSQI), Sleep Hygiene Index (SHI). Additionally, RA patients and healthy controls were estimated by HAQ-DI, Beck Anxiety and Beck Depression Inventory, PSQI, and SHI. Logistic regression analysis was used to determine the predictors of sleep quality. Results: Preliminary results of the study were given. The baseline demographics were similar among groups. When comparing groups according to HAQ-DI, Beck Anxiety and Beck Depression Inventory, PSQI, and SHI, we found higher scores in SSc and RA rather than healthy controls (p<0.001, p=0.001, p=0.001, p<0.001, p=0.003; respectively). While depression and sleep hygiene were determined as the risk factors of sleep quality in SSc in univariate analysis, depression (OR=1.380, 95%CI: 1.065−1.784, p=0.015) and sleep hygiene (OR=1.201, 95%CI: 1.003−1.439, p=0.046) were also found in multivariate logistic model. In RA patients, while health status, depression, and anxiety were found as risk factors according to the univariate analysis, depression (OR=1.120, 95%CI: 1.006−1.245, p=0.038) was the only factor according to multivariate logistic model (Table). Conclusion: Although depression is a well-known clinical variable impacting on sleep quality, sleep hygiene should also be kept in mind as a confounding factor. References: [1]Milette K, Hudson M, Körner A, et al. Sleep disturbances in systemic sclerosis: evidence for the role of gastrointestinal symptoms, pain and pruritus. Rheumatology (Oxford). 2013 Sep;52(9):1715-20. [2]Sariyildiz MA, Batmaz I, Budulgan M, et al. Sleep quality in patients with systemic sclerosis: relationship between the clinical variables, depressive symptoms, functional status, and the quality of life. Rheumatol Int. 2013 Aug;33(8):1973-9. Disclosure of Interests: None declared